Tantangan dalam Implementasi Kurikulum Merdeka Di Sekolah Dasar - Friska Ria Sitorus (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
Curriculum change is a necessity that is interpreted as curriculum development and must be implemented since it is demand of the times. However, in implementing the curriculum changes, before the 2006 curriculum to the 2013 curriculum, there were problems faced. This research aims to examine the problems of implementing the Independent Curriculum faced by schools, teachers, and students. The data were collected through the fourth-grade teachers and the school principal. This research site is at SD Negeri 2 Pilot Blangkejeren. Data collection techniques use interviews and observation. This research figures out, firstly, frequent changes in regulations and repeated revisions of regulations, uneven training for teachers, incomplete facilities and infrastructure, handbooks for teachers and students handbooks, changes in scientific culture, school literacy movements, and internal supervision are not yet completed, optimal. Secondly, most students are from middle-class families background who have less learning support from their parents. Besides, in the learning process conducted in the teacher center learning students are passive.